Dissociative symptoms mediate the relation between PTSD symptoms and functional impairment in a sample of military members, veterans, and first responders with PTSD. Issue 1 (1st January 2018) - Boyd, Jenna E.; Protopopescu, Alina; O'Connor, Charlene; Neufeld, Richard W. J.; Jetly, Rakesh; Hood, Heather K.; Lanius, Ruth A.; McKinnon, Margaret C.
ABSTRACT: Background : Posttraumatic Stress Disorder (PTSD) is associated with significant functional impairment in important areas, including interpersonal relationships and occupational or educational roles. Preliminary evidence suggests that the dissociative subtype of PTSD (PTSD+DS), characterized by marked symptoms of depersonalization and derealization, is associated with increased functional impairment and disease severity, including among military members and veterans diagnosed with PTSD. Similarly, first responders (e.g. police, fire, paramedics) have also been found to experience dissociative symptoms. Despite these findings, little work has investigated whether dissociative symptoms are related to heightened functional impairment among these populations. Objective : We examined the relation between functional impairment and symptom level variables, including dissociative symptoms of depersonalization and derealization among military members, veterans, and first responders with probable PTSD. We further investigated the hypothesis that dissociative symptoms mediate the relation between PTSD symptomatology and functional impairment. Method : Eighty-one medical charts of inpatients at a residential PTSD treatment programme were accessed via retrospective review. Sixty-two were included in the present analyses. Comparison of means on symptom measures between first responders and military members/veterans were conducted, followed by correlational and mediation analyses. Results : Compared with first responders, military members and veterans showed higher levels of derealization, functional impairment, alexithymia, anxiety, and depression. Within the total sample, dissociative symptoms emerged as the strongest correlate of functional impairment and, among the dissociative symptom clusters, derealization symptoms demonstrated the strongest relation with impairment. Mediation analyses revealed that total dissociative symptoms and derealization symptoms significantly mediated the relation between PTSD symptoms and functional impairment. Conclusions : These findings highlight the importance of assessing and treating dissociative symptoms, consistent with the dissociative subtype of PTSD, among military members, veterans, and first responders with PTSD. Successful recovery on a functional and symptomatic level may necessitate treatment of dissociative symptoms, particularly derealization.